CLUSTER OF INDONESIA KABUPATEN-KOTA POTENTIAL IN DEVELOPING FOOD CROP AND HORTICULTURE COMMODITIES - Imam Wahyudi; Nunung Nuryartono; Amzul Rifin (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
Identification of potential areas in an agricultural sector is needed in order to meet the national food needs, among others, by carrying out mapping the potential areas through clustering the Kabupaten-Kota in Indonesia, especially on imported agricultural commodities of food crops and horticultures. The use of cluster analysis with top-down clustering method (K-means) produces the best cluster. Of 268 regencies-cities, there are 7 clusters, namely Cluster 1 consisting of 154 regencies, Cluster 2 consisting of 2 regencies, Cluster 3 consisting of only1 regency, Cluster 4 consisting of 8 regencies, Cluster 5 consisting of 24 regencies, Cluster 6 consisting of 75 regencies, and Cluster 7 consisting of 4 regencies. Each cluster has its own dominant commodity characteristics.  The results of typology klassen on constructed clusters show that food crop and horticulture commodities have grown well and fast. Out of 13 commodities, there are 7 major commodities: Cluster 1: rice and corns; Clusters 2, 3 and 7: cassava; Cluster 4: corns, cassavas and chilly; Cluster 5: apples; Cluster 6: corns, shallots, and garlic. Six other commodities do not grow well, namely sorghum, potatoes, soybeans, peanuts, oranges, and grapes. The potential lack of an area is due to the plants’ low productivity, which is mainly because of plant pests, highly operational cost, climates and natural disasters. Keywords: imports, food crops, horticulture, cluster, and leading sector.